Os ciclos de receitas e gastos com pessoal e os reflexos na produtividade: um estudo de caso comparativo entre escritórios de advocacia - Mauro, Mario Luiz Iaconis (2010)
The proposal of this work is the production of a case study in two law offices of different dimension considering the number of lawyers in order to get how the revenue and payroll cycle are presented and what are the impacts on the measure of professional productivity and the fiscal aspects adopted. After getting the information about the main activities connected to the cycles studied, it was done a comparison with theoretical basis extracted from books, articles, sites and specialized magazines, mainly in the national ambit and some sources from North America. By using of case study tool, that was the use of a questionnaire with seven questions directed to the administrators of the fifties law offices more admired in Brazil in 2009, it has got some data related to more relevant aspects of revenue and payroll cycle, besides the questions of the fiscal aspects adopted and the professional productivity. The intention was to compare the law offices studied with the answers collected from the other offices selected from the list of the most admired of the country in 2009 of Anuário - Análise Advocacia 500 and to cross the data obtained by the case study with the theoretical sources developing the analysis of the results obtained